2020
DOI: 10.1111/pcn.13025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcranial direct current stimulation of prefrontal cortex on risk‐taking behavior

Abstract: Aim Recent cognitive neuroscience research shows that noninvasive brain stimulation can modify a wide range of behaviors in healthy people. Such regulation effects on human behaviors provide new insights into the neurobiology of cognitive processes and establish causal brain–behavior relations. Here, we aimed to examine the effects of transcranial electrical stimulation (TES) of the prefrontal cortex on risk‐taking. Methods We performed a systematic search on the PubMed, Web of Science, and Cochrane databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 73 publications
2
22
0
Order By: Relevance
“…On the basis of the present data, such discrepancies could be of relevance to clinicians, by providing tDCS activation of the rDLPFC to patients who need to recover more inhibitory neural resources, while patients exhibiting compensatory mechanisms may need to reduce the activity allocated to the task and they should hence be offered active tDCS over the rIFG. Our results are in line with the conclusion drawn by Khaleghi et al 11 as their meta-analysis demonstrates a significant effect of unilateral tDCS over DLPFC on risk-taking behavior in healthy subjects and as authors stress the relevance of such findings for clinical disorders such as addictive behaviors. Clearly, such speculative data should be tested in further studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the basis of the present data, such discrepancies could be of relevance to clinicians, by providing tDCS activation of the rDLPFC to patients who need to recover more inhibitory neural resources, while patients exhibiting compensatory mechanisms may need to reduce the activity allocated to the task and they should hence be offered active tDCS over the rIFG. Our results are in line with the conclusion drawn by Khaleghi et al 11 as their meta-analysis demonstrates a significant effect of unilateral tDCS over DLPFC on risk-taking behavior in healthy subjects and as authors stress the relevance of such findings for clinical disorders such as addictive behaviors. Clearly, such speculative data should be tested in further studies.…”
Section: Discussionsupporting
confidence: 93%
“…6 While CRPs may promote the development of an automatic association between a specific cue and a No-go response 7 by enhancing frontal top-down inhibitory control, 8 active tDCS over the right inferior frontal cortex (rIFC) or the right dorsolateral prefrontal cortex (rDLPFC) is thought to induce specific neural modifications including the fronto-basal-ganglia network. 9,10 In a recent meta-analysis, Khaleghi et al 11 highlight that unilateral tDCS over DLPFC leads to less risk-taking behaviors in healthy individuals through the neuromodulation of the meso-cortico-limbic dopamine system. Combining training with tDCS is nowadays thought to improve training outcomes through synergistic effects, as tDCS may enhance the training effect by facilitating learning through specific neuroplastic changes, while training could magnify the acute effect of the neuroplasticity intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, various studies suggest tDCS may be a useful tool to treat neuropsychiatric conditions. These studies have also shown cognitive improvement in some psychiatric conditions after tDCS interventions [27]. However, tDCS is not currently an FDA-approved treatment.…”
Section: Introductionmentioning
confidence: 98%
“…It is very difficult to deal with these challenges without theoretical models, conceptual frameworks and powerful computational tools. Although experimental studies yield valuable and useful information to understand the cognitive processes and biological disturbances in mental illness [7][8][9][10][11], they are usually limited by practical, economic or ethical factors. In recent years, computational neuroscience has shown great promise in the field of psychiatry research and computational psychiatry by establishing a connection between pathophysiological and phenomenological aspects of mental illness, thereby reshaping current nosology in more biologically dimensions.…”
Section: Introductionmentioning
confidence: 99%